Youth Empowerment Through Papaya Cultivation with Agribusiness Innovation for Economic Independence - Muhammad Husaini Assauwab; Mario Pani; Mega Wati (Journal of Community Service and Rural Development, 2025)
This community service activity aims to empower the youth of Tanjung Aman Village, Darul Hasanah District, Southeast Aceh Regency through papaya cultivation as an agribusiness innovation that supports economic independence. This topic was chosen due to the low participation of youth in the agricultural sector due to a lack of understanding of the promising potential of agribusiness. The methods used included counselling, hands-on training, and assistance in managing papaya cultivation. Evaluation was conducted quantitatively and qualitatively to measure improvements in knowledge, skills, and youth participation. The results showed an 80% increase in understanding of cultivation techniques, 75% increase in practical application on personal land, and 25% increase in land productivity. This activity also encouraged economic independence with 60% of participants having developed agribusiness business plans. These results show that the practice-based training approach is effective in improving youth competence in agriculture, so it can be a sustainable empowerment model in rural areas.